S-Parameter Analysis of Parallel Coupled Line Bandpass Filter With Comsol Multiphysics - Teh, Mun Hoe; Abdul Kahar, Rosmila; Mohd Alhata, Nurafiqah; Rozali, Mohamad Mazlan (Enhanced Knowledge in Sciences and Technology, 2023)
Nowadays as the global internet growing in high speed and the 5G flourish the demand of high-speed data transfer with low delay are still in progress. Microwave filters are currently having problems such as insufficient of bandwidth due to the wide range of transmission signal frequency, large insertion loss. At the same time, parallel coupled line bandpass filters are being used to meet the requirement. For a wider range of frequency for passband and a more stable insertion loss, 5G parallel couple line bandpass filters with Patterned Ground Structure (PGS) technique using COMSOL Multiphysics software is designed and compared with reference filter. The effect of substrate size, strip/slot size and shape on S-parameter and electromagnetic field simulation results are presented and filter(s) design with better S-parameter is proposed. The small square strip medium substrate filter has 8.7% of improvement on the lowest S11 compared to reference filter, whereas the big O strip medium substrate has 20.3% and 8.7% of improvement for both maximum S11 and minimum S11 compared to the reference filter.